2017
DOI: 10.3945/ajcn.116.142034
|View full text |Cite
|
Sign up to set email alerts
|

Total and subtypes of dietary fat intake and risk of type 2 diabetes mellitus in the Prevención con Dieta Mediterránea (PREDIMED) study

Abstract: The associations between dietary fat and cardiovascular disease have been evaluated in several studies, but less is known about their influence on the risk of diabetes. We examined the associations between total fat, subtypes of dietary fat, and food sources rich in saturated fatty acids and the incidence of type 2 diabetes (T2D). A prospective cohort analysis of 3349 individuals who were free of diabetes at baseline but were at high cardiovascular risk from the PREvención con DIeta MEDiterránea (PREDIMED) stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
69
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 42 publications
5
69
0
2
Order By: Relevance
“…This particular pattern was nominally associated with increased levels of insulin, a finding consistent with current literature, suggesting meat consumption to be associated with hyperinsulinaemia and type 2 diabetes [38,55]. The total fat, mainly consisting of the saturated fat of the meat and the trans fatty acids of the fried potatoes, is believed to contribute to the increased prevalence of insulin resistance and type 2 diabetes [56][57][58].…”
Section: Discussionsupporting
confidence: 83%
“…This particular pattern was nominally associated with increased levels of insulin, a finding consistent with current literature, suggesting meat consumption to be associated with hyperinsulinaemia and type 2 diabetes [38,55]. The total fat, mainly consisting of the saturated fat of the meat and the trans fatty acids of the fried potatoes, is believed to contribute to the increased prevalence of insulin resistance and type 2 diabetes [56][57][58].…”
Section: Discussionsupporting
confidence: 83%
“…European and American studies have also confirmed that intakes of total fat, animal fat and SFA are risk factors for the development of diabetes mellitus . In addition, a high‐fat diet or high proportion of SFA in the diet can lead to accumulation of fat in the adipose tissue, muscle and liver, which can cause insulin resistance. Our study of mice that received a high‐fat diet also confirmed that it impaired the insulin–protein kinase B signaling pathway, and reduced the phosphorylation/activation of adenosine monophosphate‐activated protein kinase, which led to insulin resistance.…”
supporting
confidence: 77%
“…T2DM is an increasing epidemic in developed countries and is closely linked to obesity (diabesity). Most epidemiological studies and systematic reviews promote the view that milk and dairy products are good for metabolic health and may reduce the risk of T2DM [142][143][144][145][146][147]. Dairy product intake may be inversely associated with risk of T2DM, but the evidence is inconclusive for total dairy products and sparse for individual types of dairy products.…”
Section: Type 2 Diabetes Mellitusmentioning
confidence: 99%